Geological, geophysical, and geochemical constraints on the time-space evolution of Akan composite caldera, Hokkaido, Japan - Hasegawa, Takeshi; Nakagawa, Mitsuhiro; Kamiyama, Hiroyuki; Yamamoto, Akihiko (Frontiers in Earth Science, 2022)
Some calderas are geometrically complex that may be related not to a single eruption, magma body, or structure. In order to reveal their forming processes, multidisciplinary methods should be applied. Akan volcano has E-W elongated and irregular-shaped caldera (24 × 13 km), implying a complex mechanism of formation. Akan caldera results from successive explosive eruptions from 1.4 to 0.1 Ma. On the basis of duration of dormancy and petrological features (mainly whole-rock major element compositions) of juvenile materials, these eruptions have been grouped into 17 eruptive groups (Ak1–Ak17), each of which consists of a single or a sequential phase. In order to investigate the processes of caldera formation, we focus on the younger eruptive groups (Ak1–Ak7: 0.8 to 0.2 Ma) that have relatively large magnitudes (>10 km3) and likely control the present caldera shape. We performed component analysis of lithic fragments from pyroclastic fallout deposits, whole-rock trace element analysis of juveniles, and gravitational survey of the caldera. We grouped Ak1–Ak7 into three types, namely, type A (Ak1, Ak2), type B (Ak3–Ak5), and type C (Ak6, Ak7), based on the lithic componentry, most of which are accessary and accidental fragments from vent and conduit areas. The characteristic lithic component in each type is as follows: altered rock in type A, aphyric dacite in type B, and pyroxene andesite in type C. These data suggest that explosive eruptions of each type are derived from distinct sources. The whole-rock composition of juvenile materials of each type also shows distinct trends on Harker diagrams. These three chemical trends are nearly parallel, suggesting that three different magma systems were active. This is consistent with the lithic componentry showing three spatially distinct vent sources. The geological and petrological evidence is supported by a Bouguer anomaly map. Akan caldera is characterized by three circular closed minima, indicative of three depressed segments that correspond to the source regions, each of which possibly discharged the three types of magma. Caldera-forming eruptions of Akan caldera occurred from at least three distinct sources with distinct magma systems. In conclusion, Akan caldera is a composite caldera, and its shape reflects the distribution of multiple source regions. The case study of Akan caldera shows a possible time-space evolutionary pathway for a caldera complex where several smaller calderas are nested.